Glucose and lipopolysaccharide differentially regulate fibroblast growth factor 21 in healthy male human volunteers – A prospective cross‐over trial. Issue 24 (22nd November 2022) - Pohlhammer, Johannes; Heinzl, Matthias Wolfgang; Klammer, Carmen; Feldbauer, Roland; Rosenberger, Klemens; Resl, Michael; Wagner, Thomas; Obendorf, Florian; Egger‐Salmhofer, Margot; Dieplinger, Benjamin; Clodi, Martin
Abstract: Fibroblast growth factor 21 (FGF21) affects the regulation of metabolism. Additionally, anti‐inflammatory properties are attributed to FGF21, and studies in animals and humans show conflicting results. This study aimed to investigate how FGF21 is affected by glucose and lipopolysaccharide (LPS) in humans. Therefore, FGF21 was measured eight times at different time points within 48 h in this prospective cross‐over trial after glucose and LPS on two different study days. The study included ten healthy, non‐smoking male subjects aged 18–40. Repeated measures analysis of variance and paired t ‐test as post hoc analysis were applied. The administration of glucose and LPS resulted in a significant difference in regulating FGF21 ( p < 0.001). After glucose administration, FGF21 declined sharply at 360 min, with a subsequent steep increase that exceeded baseline levels. LPS induced a drop in FGF21 after 180 min, while the baseline concentrations were not reached. After 180 min and 24 h, a statistically significant difference was demonstrated after adjusting the Bonferroni–Holm method. So, our results support the hypothesis that glucose and LPS differentially affect the human expression of FGF21 over 48 h.